KINERJA KEUANGAN PERBANKAN DENGAN METODE RGEC SEBELUM DAN SELAMA COVID-19 (STUDI KASUS PADA BANK UMUM YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2023) - Hotma Indah Sari Sinaga; Nona Jane Onoyi; Mursal (Mount Hope Management International Journal, 2024)
The purpose of this study is to examine banks' financial results on the IDX both before and after COVID-19. The RGEC analysis approach is being used for the period of 2016–2023. The approach used in this research is quantitative. With a population of 47 commercial banks, the sample was obtained using purposive sampling methods. Of the samples that satisfied the requirements, 17 commercial banks for the years 2016–2023 were included, and the data type was secondary data. The data collecting approach makes use of descriptive analysis methods to extract information from commercial bank financial statements available on the IDX for the years 2016–2023. The "Wilcoxon Signed Rank Test" is a hypothesis testing tool that compares the overall financial performance of commercial banks. According to the results of the data analysis performed using SPSS v26, there is no significant change between NPL, GCG, and ROA before and during the COVID-19 period of 2016–2023. There are notable distinctions between LDR and CAR both before and throughout the COVID-19 timeframe of 2016–2023.